Agent Protection in an Agency Agreement - Manurung, Samuel Karunia; Yunanto, Yunanto (Journal of Social Research, 2023)
Marketing products through agency business agreements is a common practice when manufacturers seek to expand their reach within specific territories. In Indonesia, this arrangement is often driven by import and export restrictions imposed on international entities. Due to these restrictions, foreign entities, referred to as principals, must engage agents or representatives to facilitate the sale of their products within Indonesia. This agency relationship is predominantly built upon a contractual agreement. In this agreement, the agent commits to representing the principal's interests, including legal representation if necessary. Conversely, the principal consents to the agent's representation on their behalf, particularly in legal matters. To gather insights into this dynamic, a Conceptual Approach method is employed to collect data. It emphasizes the significance of legal certainty within the framework of formal agreements. In Indonesia, contract law protection is founded upon this concept, ensuring that agreements are upheld. In the event of disputes arising from agency agreements, resolution processes typically defer to the terms stipulated in the initial agreement, emphasizing the importance of a well-defined and legally sound contract.